Strategic value of Online Social Networks (OSNs) in supply chain networks during COVID-19 - Md. Ziaul Haque; Md Shariful Islam; Santus Kumar Deb; Md. Rashidul Islam (Cogent Business & Management, 2022)
The coronavirus (COVID-19) epidemic has transmuted the business environment and disordered supply chains worldwide. Over the last decade, online social networks (OSNs) have impacted every element of human life and corporate organization. Deploying OSNs services in supply chain networks is currently a pressing need. This study developed a model based on the IS success model, resource-based view, and absorptive capacity to explore the strategic value of OSNs in the supply chain network during COVID-19. Structural Equation Modeling (SEM) analyzes 220 data collected using online questionnaires. Information, system, and service quality emerged as influential features of online social networks that enhance the absorptive capacity and supply chain visibility and agility. The performance of the supply chain is positively impacted by each of OSN's strategic values, including visibility, agility, and absorptive capacity during COVID-19. In addition, absorptive capacity and supply chain visibility and agility mediate the association of information, system, and service quality features with supply chain performance. Supply chain managers and policymakers will better grasp OSNs adoption necessities and features during pandemic situations. It will also contribute to operation management, information systems, and social media by presenting OSNs in a supply chain environment.
Keywords: 650; COVID-19; OSNs; strategic value; supply chain network; supply chain performance